O arco-íris é meu ambiente : as aprendizagens e as narrativas de militantes LGBT+ sobre identidades, lutas e sonhos de um mundo policrômico - Jales, Romário Custódio (2021)
This research involves three major axes that are connected, although they can sometimes be distant: environmental education, LGBT+ and climate crisis. Through environmental education we seek to understand how the LGBT+ community interprets the climate phenomenon. We start from the premise that the narratives of their experiences have essential pedagogical values for the LGBT+ movement to incorporate the climate dimension in its agendas and the ecological movement also incorporates the LGBT+ community in its policies. In summary, we seek to build learning through the narratives of a group of LGBT+ people in the phenomenological triad I OTHERS-WORLD in dialogue with the Michèle Sato's Cartography of Imaginary. In our research, seven LGBT+ activists, named here with the colors of the rainbow, told us about their experiences, their discoveries and their struggles, tracing a cartography that took us on an epistemic and phenomenological journey of the environment they lived and shared. As already recorded in other research with minorities carried out by the GPEA, the climate crisis is an issue that is invisible in the agendas and experiences of most communities. This research confirms this invisibility of the climate agenda also among the LGBT+ people surveyed. The result of this work may serve as a subsidy for new research related to the proposed themes and promote, through the scientific elements offered, a union between LGBT+ activism and environmental activism.